Factors associated with delayed first ophthalmological consultation for primary glaucoma: a qualitative interview study - Liu, Hua; Chen, Chen; Chen, Zhuo; Li, Qian; Li, Quan; Liu, Wei (Frontiers in Medicine, 2023)
Background Glaucoma has an insidious onset with non-specific early symptoms, often leading patients to delay in seeking help. However, postponing the first ophthalmological consultation can result in delayed diagnosis and treatment, with adverse effects on vision. This study explored the factors associated with delayed first ophthalmological consultation in patients with primary glaucoma, with the overarching aim of informing measures to reduce delayed consultation and avoid the consequent adverse outcomes. Methods We adopted a phenomenological approach. Semi-structured interviews were conducted with patients admitted to a tertiary eye hospital in Tianjin, China, from January 2021 to April 2021. Data were analyzed by Colaizzi’s seven-step method. Results We identified 46 patients with primary glaucoma who delayed their first ophthalmological consultation for various reasons. There were four major themes and 16 sub-themes. The major themes were as follows: (1) occult symptoms that are difficult to identify; (2) insufficient knowledge and understanding of glaucoma-related risks and harm; (3) perceived difficulties in accessing medical care; and (4) inadequate support system. Conclusion In order to avoid patient delay and consequent irreversible damage to the visual field in patients with primary glaucoma, it is essential that medical staff identify symptoms more effectively, change habitual medical behavior of the patients, adopt a medical union model, and promote the use of a social medical support system to address practical difficulties in delivering adequate care.